Indenter radius effect on mechanical response of a-(11–20), c-(0001), and m-(-1100) plane GaN single crystals in nanoindentation: A molecular dynamics study. (July 2022) - Li, Rui; Wu, Gai; Liang, Kang; Wang, Shizhao; Xue, Lianghao; Sun, Yameng; Dong, Fang; Li, Hui; Liu, Sheng
Abstract: Molecular dynamics (MD) simulation was used to systemically investigate the nanoindentation process of GaN. Different loading orientations and indenter radii were simulated and studied. In this work, the variation of stress propagation, particle movement and evolution of dislocations were discussed in detail. The size of the indenter has an important influence on the occurrence of plastic deformation. As the size of the indenter increases, the critical load of plastic deformation increases and the critical shear strain decreases. In addition, the nucleation and propagation of dislocations during initial plastic deformation is always along the low-strain region. The propagation of dislocation varied in a similar trend as the atomic displacement and atomic stress. The nano-hardness value of GaN during the indentation process was significantly affected by the size effect. Among them, the polar plane of GaN has higher hardness and the dislocations were pinned to the sample surface, which would not slip and propagate into the sample. However, during the indentation process perpendicular to the a-plane and m-plane, there were two types of dislocations in the sample, which were nailed to the surface or propagated to the inside of the sample. Graphical abstract: (a) MD simulation model of diamond indenter against wurtzite GaN specimen, (b) Structural diagram of wurtzite GaN specimen with different crystal orientations. Image 1 Highlights: The initial defect nucleation of GaN has a certain preferred orientation. The propagation direction of stress was accurately obtained by MD simulation. Indenter radius affects critical shear strain for dislocation nucleation. The relationship between stress propagation and dislocation evolution was revealed. Provide a clear theoretical basis for the exploration of failure mechanism.